A Study on Autonomic Dysfunction in Type 2 Diabetes Mellitus with Peripheral Neuropathy - Suby Kuriakose; Anuj Singhal; Naresh Bansal; Rajat Shukla; Shilpa M Paul; Aditya Singhal (Journal of Marine Medical Society)
Introduction: Subclinical Autonomic Neuropathy is found in association with distal symmetric polyneuropathy in diabetic patients. The Aim of this study was to compare the Cardiac Autonomic Function Test parameters in Type 2 Diabetes Mellitus patients with and without Distal Peripheral Neuropathy. The Primary Objective was to compare the mean of Valsalva ratio in Type 2 Diabetes Mellitus patients with and without Distal Peripheral Neuropathy. The secondary Objective of this study was to find the correlation between Michigan Neuropathic Screening Instrument Score and Autonomic Function test parameters in type 2 Diabetes Mellitus patients. Methods: This was a single centre, cross sectional study conducted from July 2022 to Feb 2023. The study was commenced after obtaining Institute Ethics Committee clearance. Subjects who satisfied the inclusion and exclusion criteria, and gave informed consent for participation in this study were eligible for enrolment. The inclusion Criteria were patients aged between 18 and 65 years with diagnosis of Diabetes mellitus. The number required to study Diabetic patients with peripheral neuropathy was 34 and for Diabetic patients without peripheral neuropathy was 34. Total sample size of 68 patients was taken. Once the patient was enrolled a detailed history, clinical examination, ANS testing and MSNI scoring was done as per attached pre verified proforma duly vetted by institutional scientific committee. Patients were asked to refrain from vigorous exercise for the 24 hours before to the cardiovascular testing as well as from eating, drinking, or smoking for at least 2 hours before the autonomic testing. At the conclusion of the checkup, all antidiabetic and other prescriptions were given. After data collection, test for normality of data was done. Appropriate statistical tests were applied according to data distribution and analysed by using SPSS criteria 2011. Results: A total of 68 patients, 34 with symptoms of Diabetic Peripheral Neuropathy and 34 without Diabetic Peripheral Neuropathy were studied from July 2022 to December 2023. The age, BMI, duration of disease, HbA1c, resting systolic blood pressure and heart rate didn’t show any significant difference between the two groups and thus the groups were comparable. The median (interquartile range) of MNSI score of diabetic patients without neuropathy was 1(1,1) and diabetic patients with neuropathy was 8 (7,9) with p value < 0.005. There was a significant difference in E: I ratio (P<0.0001) between diabetic patients with and without neuropathy. The mean ± SD of Valsalva ratio, in diabetic patients without neuropathy was 1.632 ± 0.115 and with neuropathy was 1.366 ± 0.045. There was a significant difference in Valsalva ratio (P<0.0001). There was a good negative correlation between MNSI score and Valsalva ratio with r= -0.769 and p value < 0.0001 in Type 2 Diabetes mellitus patients. Conclusion: This study found that the Cardiac Autonomic Function Test parameters in Type 2 Diabetes Mellitus patients with and without Distal Peripheral Neuropathy, were significantly deranged in patients with symptomatic DPN. The mean of Valsalva ratio was significantly different in two study groups. The correlation between Michigan Neuropathy Screening Instrument Score and Autonomic Function test parameters in Type 2 Diabetes Mellitus patients showed strong negative correlation. The patients with symptomatic DSN were found to have higher MSNI scores, who in turn were having severe cardiac autonomic dysfunction. Recommendation of Study: Mean Valsalva ratio and MNSI testing are recommended to be used as a screening tool to assess cardiac autonomic functions as a low cost tool in patients of T2DM having symptoms suggestive of DSN.